Differences in Symptom Report by Survivors With and Without Probable Intimate Partner Violence-Related Brain Injury - Chiou, Kathy S. (Violence against women, 2023)
Survivors of intimate partner violence (IPV) are at heightened risk of sustaining a brain injury (BI). Problematically, a high overlap between BI and trauma symptoms leads to difficulties in identifying when an IPV-related BI has occurred. This paper investigated differences in symptom reports between survivors with (n = 95) and without (n = 42) probable IPV-related BI. Chi-squared analyses isolated a constellation of symptoms found to be specifically associated with BI status. These symptomatic markers may assist professionals in discerning BI from other comorbid conditions present in IPV, and thus help survivors access BI-specific treatments and resources.